Is there an association between dietary intake and academic achievement: a systematic review. Issue 2 (7th September 2016) - Burrows, T.; Goldman, S.; Pursey, K.; Lim, R.
Abstract: Background: The majority of literature examining the effect of dietary behaviour on academic achievement has focused on breakfast consumption only. Here, we aim to systematically review the literature investigating the broader effects of dietary intake and behaviours on school‐aged children's academic achievement. Methods: A search was undertaken across seven databases using keywords. For studies to be included, they needed to be conducted in: school‐aged children (5–18 years); assess and report: (i) a measure of academic performance; (ii) a measure of dietary intake/behaviour; and (iii) the association between dietary intake/behaviours and academic performance. Forty studies were included in the review. Results: The majority of studies were cross‐sectional in design ( n = 33) and studied children aged >10 years, with very few reports in younger age groups. More than 30 different dietary assessment tools were used, with only 40% of those using a validated/standardised assessment method. Half the studies collected outcomes of academic achievement objectively from a recognised educational authority, whereas 10 studies used self‐reported measures. The dietary outcomes most commonly reported to have positive associations with academic achievement were: breakfast consumption ( n = 12) and global diet quality/meal patterns ( n = 7), whereas negative associations reported with junk/fast food ( n = 9). Conclusions: This review highlights that moderate associations exist for dietary intakes characterised by regular breakfast consumption, lower intakes of energy‐dense, nutrient‐poor foods and overall diet quality with respect to outcomes of academic achievement. Future studies should consider the use of validated dietary assessment methods and standardised reporting of academic achievement.